Media education and digital inclusion: Tackling the social exlusion of disadvantaged grous in Europe - Simões, Rita Basílio (2020)
Media literacy has been one of the main strategies for promoting the inclusion of disadvantaged groups in Europe. These policies that favour empowering uses of media and information are based on the knowledge that it is not enough to guarantee access to ICTs. Cultural and social environments can say a lot about the uses of the media and how the information is used as a capital for personal and collective development and empowerment. Social exclusion is a multidimensional process. Following the European values that place knowledge at the heart of social and economic development, international institutions have focused on policies that promote social cohesion by favouring empowering personal uses of the media. In recent years, fighting the digital divide became less about access and more about its uses. The role of media and technology in the process of social development is not underestimated. They are seen as instruments for having citizens that are more active and participative. This paper analyses recommendations and proposals that address social inequalities in the European Union through the promotion of media literacy. This analysis shows that there is a consensus regarding the acquisition of skills that can promote critical thinking and offers a deeper understanding of the various dimensions that are favoured in the European context.